Solving University Examination Timetabling Problem Using Intelligent Water Drops Algorithm - Aldeeb, BA; Norwawi, NM; Al-Betar, MA; Bin Jali, MZ (Springer-Verlag Berlin, 2024)
This research article aims at proposing Intelligent Water Drops (IWD) algorithm to solve the university examination timetabling problems (UETP). IWD is a recent metaheuristic population-based algorithm belonging to swarm intelligent category which simulate river system. Examination timetabling is a combinatorial optimization problem that is concerned with allocating exams to timeslots efficiently. As an initial study, the IWD Algorithm is tailored to solve uncapacitated examination timetabling problem by using carter 1996 dataset and is able to produce acceptable results, though they were not better than the the results that already reported in the literature. Some examination timetabling heuristic methods such as Saturation degree concepts have been embedded in IWD to ensure the feasibility, while the IWD operators have been trigged to iteratively improve the results.